TEOLOGI NEO AL-MA’UN DAN REPRESENTASI KEMISKINAN DALAM RUANG MEDIA - Qusyaeri, Nurdin; Tabroni, Roni (AL-IBANAH, 2021)
This paper is intended to explore the conceptual aspects of mass media representation in raising the reality of the poor and the life of the religious community. The mass media, with their enormous influence, especially in changing society, has the opportunity to take sides with a theological teaching that can answer various social problems. This research uses qualitative methods with a descriptive approach. The study conducted is a literature study, by raising ideal concepts from journals and books. This paper reveals an academic finding regarding the position of the mass media in the midst of theological struggle, where poverty and other new problems arise as a result of globalization, so the mass media must position their alignments firmly. A neo Al-Maun theological teaching that tries to be offered to bring religious communities to be more sensitive to social problems and can provide solutions as a reflection of their ritual worship, is reflected by the mass media through its various contents. So here, the mass media is present to be part of the solution to poverty and other new problems. What distinguishes the findings of this study is the impartial aspect of the journalism concept and can be reflected in more concrete journalistic works. Whereas the mass media is not a neutral entity, but has been deliberately designed from the start to be a means of struggle and to emphasize the alignments, especially to the poor and those experiencing other problems.